Use of combinatorial pharmacogenomic testing in two cases from community psychiatry - Fields ES; Lorenz RA; Winner JG (Dove Medical Press, 2016)
Eve S Fields,1 Raymond A Lorenz,2 Joel G Winner2 1Northwest Center for Community Mental Health, Reston, VA, USA; 2Assurex Health, Mason, OH, USA Abstract: This report describes two cases in which pharmacogenomic testing was utilized to guide medication selection for difficult to treat patients. The first patient is a 29-year old male with bipolar disorder who had severe akathisia due to his long acting injectable antipsychotic. The second patient is a 59-year old female with major depressive disorder who was not responding to her medication. In both cases, a proprietary combinatorial pharmacogenomic test was used to inform medication changes and improve patient outcomes. The first patient was switched to a long acting injectable that was not affected by his genetic profile and his adverse effects abated. The second patient had her medications discontinued due to the results of the genetic testing and more intense psychotherapy initiated. While pharmacogenomic testing may be helpful in cases such as these presented here, it should never serve as a proxy for a comprehensive biopsychosocial approach. The pharmacogenomic information may be selectively added to this comprehensive approach to support medication treatment. Keywords: pharmacogenomics, adverse effects, risperidone, nortriptyline, paliperidone